A Cognitive Model for Developing University Students’ Communication Skills - Essa, Eman Khaled (International Journal of Social Learning (IJSL), 2022)
This paper aims to investigate the effectiveness of a learning model in developing students’ communication skills and reducing their communication apprehension level. This model consists of three main elements, each of which has sub-elements. It takes the students through three different phases starting with raising awareness and reaching autonomy. A training program and an assessment battery were developed and administered. Both qualitative and quantitative methods were used to analyze data. There were significant differences among the pre, post, and follow-up measurements. The pedagogical implications of the study have been discussed.